Anmeldelse af Patrycja Szarek-Mason: The European Union’s Fight Against Corruption. The Evolving Policy Towards Member States and Candidate Countries - Lars Bo Langsted (Nordisk Tidsskrift for Kriminalvidenskab)
Review of Patrycja Szarek-Mason: The European Union’s Fight Against Corruption. The Evolving Policy Towards Member States and Candidate Countries